Reflections on the postcolonial and postfeminist in the work of two South African photographers: Jodi Bieber and Zanele Muholi. - Thomik, Maxine Gabrielle (My University, 2014)
The aim of this dissertation is to investigate the extent to which discourses of postfeminism and postcolonialism inform the reception of selected portrait photographs by Jodi Bieber and Zanele Muholi. The dissertation is interested in how cross-cultural and transnational formations complicate first world feminist notions of a singular, generalised identity of ‘woman’. I intend to explore whether theories of postcolonialism and postfeminism allow for more dynamic readings of their work, as well as how this is represented in the way they portray women. The dissertation will address the relevance of postcolonialism and postfeminism in photography and what this theory offers in terms of the way the images are read. In particular, it will address how the works of these two artists represent identities of women living outside of the West, and how this expression of identity can be positioned within postcolonial and postfeminist theory.
Keywords: Bieber, Jodi.; Muholi, Zanele.; Art, South African.